How to make more of less: Characteristics of sufficiency in business practices - Beyeler, Laura; Jaeger-Erben, Melanie (Frontiers in Sustainability, 2022)
Sustainable transformation towards a circular society, in which all ecosystems and livelihoods are protected and sustained, requires the integration of sufficiency in circular production and consumption practices. Beyond the technological promises to decouple resource use from economic growth, sufficiency measures to reduce production and consumption volumes in absolute terms are necessary. Businesses integrating sufficiency act as agent of change to transform current unsustainable practices along the entire supply chain. By observing the operationalization of sufficiency in14 pioneer businesses, this study identifies dimensions and practice elements that characterize sufficiency in business practices. This study observed that the sufficiency in business practices mainly represents a rethinking of business doings on three dimensions: (1) rethinking the relation to consumption; (2) rethinking the relation to others; and (3) rethinking the social meaning of the own organization. Sufficiency practitioners understand production and consumption as a mean to fulfill basic human needs instead of satisfying consumer preferences. They co-create sufficiency-oriented value with peers in a sufficiency-oriented ecosystem and they redefine growth narratives by envisioning an end to material growth. Additionally, this study revealed that care, patience and learning competences are essential characteristics of sufficiency in business practices. Sufficiency practitioners reshape their business doings by caring for others and nature; they demonstrate patience to create slow, local, and fair provision systems; and they accept their shortcomings and learn from mistakes. Integrating elements of care, patience and learning in business practices reduce the risks of sufficiency-rebound effects. Ambivalences between the sufficiency purpose and growth-oriented path dependencies persists for sufficiency-oriented businesses. Further research should investigate pathways to overcome these ambivalences and shortcomings that sufficiency practitioners experience, for instance, by exploring political and cultural settings that foster sufficiency-oriented economic activity.